Transfection Efficiency and Transgene Expression Kinetics of mRNA Delivered in Naked and Nanoparticle Format - Phua, Kyle K.L (2013)
Transfection efficiencies and transgene expression kinetics of messenger RNA (mRNA), an emerging class of nucleic acid-based therapeutics, have been poorly characterized. In this study, we evaluated transfection efficiencies of mRNA delivered in naked and nanoparticle format in vitro and in vivo using GFP and luciferase as reporters. While mRNA nanoparticles transfect primary human and mouse dendritic cells (DCs) efficiently in vitro, naked mRNA could not produce any detectable gene product. Protein expression of nanoparticle-mediated transfection in vitro peaks rapidly within 5-7 hours and decays in a biphasic manner. In vivo, naked mRNA is more efficient than mRNA nanoparticles when administered subcutaneously. In contrast, mRNA nanoparticle performs better when administered intranasally and intravenously. Gene expression is most transient when delivered intravenously in nanoparticle format with an apparent half-life of 1.4 hours and lasts less than 24 hours, and most sustained when delivered in the naked format subcutaneously at the base of tail with an apparent half-life of 18 hours and persists for at least 6 days. Notably, exponential decreases in protein expression are consistently observed post-delivery of mRNA in vivo regardless of the mode of delivery (naked or nanoparticle) or the site of administration. This study elucidates the performance of mRNA transfection and suggests a niche for mRNA therapeutics when predictable in vivo transgene expression kinetics is imperative.